2014
DOI: 10.1371/journal.pone.0097016
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Insulin-Like Growth Factor 1 Receptor Inhibits Pancreatic Cancer Growth and Metastasis

Abstract: Pancreatic cancer is one of the most lethal cancers. Increasing incidence and mortality indicates that there is still much lacking in detection and management of the disease. This is partly due to a lack of specific symptoms during early stages of the disease. Several growth factor receptors have been associated with pancreatic cancer. Here, we have investigated if an RNA interference approach targeted to IGF-IR could be effective and efficient against pancreatic cancer growth and metastasis. For that, we eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 43 publications
(47 reference statements)
4
60
0
4
Order By: Relevance
“…The insulin-like growth factor (IGF) system has recently been implicated in the progression of PDAC (7). IGF-binding protein 2 (IGFBP2) is one of six proteins in the IGFBP family that bind IGFs with high affinity (8).…”
Section: Introductionmentioning
confidence: 99%
“…The insulin-like growth factor (IGF) system has recently been implicated in the progression of PDAC (7). IGF-binding protein 2 (IGFBP2) is one of six proteins in the IGFBP family that bind IGFs with high affinity (8).…”
Section: Introductionmentioning
confidence: 99%
“…Insulin-like growth factor-1 (IGF-1) signaling is associated with various types of cancers, including pancreatic, lung and breast cancers [1315]. Activation of IGF-1 receptor (IGF-1R) by IGF-1 binding results in cell proliferation, metastasis and drug resistance, and it is reported that IGF-1R promotes survival and proliferation of TNBC cell lines [16].…”
Section: Introductionmentioning
confidence: 99%
“…Some of such regulatory factors have also been contained in our results. MAPK signaling pathway ( hsa04010 ) has been confirmed to have crosstalk with mTOR signaling pathway as we have mentioned above and has been reported to be quite crucial for the invasion and metastasis of pancreatic cancer [80, 81]. Apart from such two functional signaling pathways, another pathway, which has been widely reported to contribute to endometrial cancer, ERBB signaling pathway ( hsa04012 ), is also in Table 1 [82].…”
Section: Resultsmentioning
confidence: 91%